Microscopic characteristics of sulfur depositions in high-sulfur-content reservoirs - Nong LI; Liqiang ZHAO; Dong HUI; Tao LI; Zhijin PU; Xiaohang DENG; Keming ZHOU (Shiyou shiyan dizhi, 2023)
A large number of high-sulfur-content carbonate gas reservoirs have been discovered in the northeastern part of the Sichuan Basin, and their reserve accounts for more than half of the total natural gas reserves in the basin. However, sulfur deposition has been a major problem for a long period which is restricting for the efficient development of high-sulfur-content gas reservoirs. In this paper, sulfur deposition experiments in carbonate rock samples were carried out with high-sulfur-content natural gas by the means of micro-CT scanning, scanning electron microscopy, gas chromatograph and energy spectrum analysis. The changes of the microscopic pore structure of the samples and gas composition before and after the experiments were quantitatively obtained, and the 3D visualization of sulfur deposition in reservoir rocks was achieved for the first time. Results show that after sulfur deposition experiment, the total sulfur content in high-sulfur-content gas decreased by 12.58%, and the organic sulfur component decreased by 9.07%. Sulfur particles were mainly deposited in rock pores with a radius of less than 500 μm, resulting in decreases in rock permeability and porosity by 34.40%-67.80% and 3.77%-7.69%, respectively. This study further improved the understanding of the microscopic characteristics of sulfur deposition and provided support for the formulation of production enhancement measures for high-sulfur-content gas reservoirs.